1988
DOI: 10.1021/bi00416a050
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of non-histone protein HMG1 revealed by the nucleotide sequence

Abstract: The isolation and sequencing of a cDNA clone coding for the entire sequence of pig thymus non-histone protein HMG1 are described. The sequence analysis reveals a complete 2192-nucleotide sequence with a 5'-terminal untranslated region of 11 nucleotides, 642 nucleotides of an open reading frame that encoded 214 amino acids, and a 3'-terminal untranslated region of 1539 nucleotides. The HMG1 protein, deduced from the nucleotide sequence, has a molecular weight of 24,785 and a C-terminal of a continuous run of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 28 publications
2
72
0
Order By: Relevance
“…There is 80.4% homology between HMG1 (214 amino acid residues) and HMG2 (209 amino acid residues), which contain lysine-rich sequences in their HMG box domains A (positions and B (positions 94-162). 18,19) It seems, therefore, that GL has a high affinity with HMG1/2, as has been demonstrated for histones (H2A and H2B) 20) and lactoferrin, 12) which have arginine-and lysine-rich domains. These characteristics of gbPs containing arginine-and lysine-rich domains are correlated closely with the observations that (i) GL has a high affinity with DNA-binding proteins, including HMG1/2 (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…There is 80.4% homology between HMG1 (214 amino acid residues) and HMG2 (209 amino acid residues), which contain lysine-rich sequences in their HMG box domains A (positions and B (positions 94-162). 18,19) It seems, therefore, that GL has a high affinity with HMG1/2, as has been demonstrated for histones (H2A and H2B) 20) and lactoferrin, 12) which have arginine-and lysine-rich domains. These characteristics of gbPs containing arginine-and lysine-rich domains are correlated closely with the observations that (i) GL has a high affinity with DNA-binding proteins, including HMG1/2 (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…3). The homologous region in these cases matches the HMG box (Jantzen et al 1990;Kolodrubetz 1990), which corresponds to the conserved domains in nuclear high-mobility group protein HMG1 (Tsuda et al 1988;Wen et al 1989) and has been demonstrated to be a DNA-binding domain in some of the family members (Wright and Dixon 1988;Jantzen et al 1990). These suggest that Stell also could be a DNAbinding protein.…”
Section: Structure Of the Stel 1 Genementioning
confidence: 77%
“…Apparently, stel 1 regulates these genes positively. 91) is aligned with the following homologs: product of the S. pom be mating-type gene m atMc, amino acid residues 95-181 (Kelly et al 1988); putative human testis-determining factor (TDF), amino acid residues 71-158 ); porcine nuclear high-mobility group protein HMG1 (middle segment), amino acid residues 86-172 (Tsuda et al 1988); S. cerevisiae nonhistone chromosomal protein NHP6A, amino acid residues 12-92 (Kolodrubetz and Burgum 1990); human nucleolar transcription factor (hUBF)(upstream binding factor), amino acid residues 104-191 (Jantzen et al 1990}. Amino acids identical or conserved between Stel 1 and at least two of the homologs are shown in white against black, whereas those identical or conserved in three or more of the homologs but not in Stel 1 are shown in white against gray.…”
Section: Stel 1 Is Inducible By Nitrogen Starvation and Repressible Bmentioning
confidence: 99%
“…Activators can also stimulate transcription indirectly by reversing the inhibitory effects of chromatin. Anionic regions rich in aspartic acid and glutamic acid residues are characteristic of many proteins that interact with chromatin, such as nucleoplasmin (8) and HMG1 (53). The acidic activator Gal4 can displace a nucleosome from the GAL1 promoter in vivo (2).…”
Section: Discussionmentioning
confidence: 99%